Relationships between the functional movement screen score and Y-Balance test reach distances - Kelleher, L. K.; Frayne, R. J.; Beach, T. A. C.; Higgs, J. M.; Johnson, A. M.; Dickey, J. P. (International Journal of Human Movement and Sports Sciences, 2017)
Background: The Functional Movement Screen (FMS) is used to evaluate key movement patterns, functional symmetry, and identify individuals that are at elevated risk of injury. The purpose of this study was to assess whether dynamic postural control is a significant component of the composite FMS score by comparing it with Y-Balance Test (YBT) reach distances. Methods: Seventy-eight participants (including 40 males) performed the standardized FMS protocol followed by the YBT. The YBT reach distances were normalized to leg length and averaged between sides and trials. The individual reach directions were evaluated, and were also summed to form an aggregate YBT distance (TotalY). Results: We observed weak correlations between the composite FMS score and normalized posterolateral reach, normalized posteromedial reach, and the TotalY (r=0.36, 0.37, and 0.36, respectively; all p